RELIGIOUS LEADERS AND COLLECTIVE ETHICS (THE DYNAMICS OF SOCIAL SPIRITUALITY IN TIDORE ISLANDS CITY) - Alwi Abdul Haq; Syahrir Ibnu; Athirah Rizki Salsabila (Social Studies and Humanities Journal (SOSHUM), 2025)
This study aims to analyze the role of religious leaders in shaping collective ethics and the dynamics of social spirituality in Tidore Islands City, North Maluku. In a socio-religious context, religious leaders function not only as spiritual guides but also as moral agents who shape social awareness, reinforce communal solidarity, and internalize public ethics amid modern social transformations. The study employs a mixed-methods approach with a phenomenological model to explore the subjective experiences of religious figures, complemented by quantitative survey data on community perceptions of their influence. Data were collected through in-depth interviews, participatory observation, and questionnaires. The findings reveal that religious leaders in Tidore exert a significant influence on the formation of social norms; however, their effectiveness largely depends on their public communication ability, social legitimacy, and openness to intergenerational dialogue. Contextually articulated spiritual values serve as a foundation for reconstructing collective ethics within the local community. This article contributes to the study of religious communication by positioning religious leaders as central actors in the moral transformation of society.